2003
DOI: 10.1002/ctpp.200310049
|View full text |Cite
|
Sign up to set email alerts
|

Intense heavy ion beams as a tool to induce high‐energy‐density states in matter

Abstract: Because of the volume character of energy deposition of energetic ions in matter, an intense heavy ion beam is a very suitable laboratory tool to create large samples of high-energy-density matter. This paper shows with the help of two-dimensional numerical simulations how such an intense heavy ion beam can be employed to achieve this goal. The beam parameters considered in this study are those of the beams that are delivered by the existing heavy ion synchrotron, SIS18 and that which will be available at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…The latter scheme, on the other hand, involves a low entropy compression of a sample material like hydrogen or water that is imploded in a multi-layered cylindrical target that is driven by a hollow beam with an annular focal spot or by a beam with a circular focal spot. The former configuration is suitable to study the problem of hydrogen metallization [35,36,38,40,41,53,54] while the latter can be used to study the interiors of the giant planets [48][49][50][51]. In the following, these schemes are described in detail.…”
Section: Proposed Experimental Schemes For the Hedgehob Collaborationmentioning
confidence: 99%
“…The latter scheme, on the other hand, involves a low entropy compression of a sample material like hydrogen or water that is imploded in a multi-layered cylindrical target that is driven by a hollow beam with an annular focal spot or by a beam with a circular focal spot. The former configuration is suitable to study the problem of hydrogen metallization [35,36,38,40,41,53,54] while the latter can be used to study the interiors of the giant planets [48][49][50][51]. In the following, these schemes are described in detail.…”
Section: Proposed Experimental Schemes For the Hedgehob Collaborationmentioning
confidence: 99%
“…Feasibility studies of such dual-beam schemes have been done for the upgraded SIS18 and the future SIS 100 at the FAIR facility, and detailed numerical simulations have also been carried out for interesting experiment designs Tahir et al, 2002Tahir et al, , 2003a In December 2003, high energy density experiments were carried out at the GSI using the most intense uranium beams generated so far. that one may allow generation of two beams, one high intensity, bunched beam that will heat the target and the other a low intensity un-bunched beam with a duration on the order of 1 ms that can be used for diagnostic purposes.…”
Section: Interaction Of Heavy Ions With Shockwave-driven Non-ideal Plmentioning
confidence: 99%
“…A multinational collaboration, named HEDP@FAIR, has been organized to oversee the construction of the experimental facilities and also to carry out theoretical work to design the future experiments. Extensive theoretical work has been performed during the past years, which has shown that using the SIS100 uranium beam one may access those parts of the phase diagram that cannot be accessed by traditional methods . As a result of these studies, ion beams are now considered to be a very efficient tool to produce HED matter samples in the laboratory.…”
Section: Introductionmentioning
confidence: 99%